THE EFFECT OF EL-NINO 2015 ON THE RUBBER PLANT (HEVEA BRASILIENSIS) GROWTH IN THE EXPERIMENTAL FIELD SEMBAWA RESEARCH CENTRE - Jamin Saputra; Charlos Togi Stevanus; Andi Nur Cahyo (Widyariset, 2016)
Dry season is a fator affecting plant growth. If climate anomaly El-Nino that causing prolonged dry season happens, the effect on the plant growth will be bigger. On 2015, El-Nino is happening. The presence of climate anomaly like La-Nina and El-Nino can be predicted by SOI (South Oscilation Index) released by Australian Bureau of Meteorology. Continued positive SOI value indicates symptomps of La-Nina climate anomaly and continued negative SOI value indicates symptomps of El-Nino climate anomaly. This research was aimed to determine the effect of El-Nino climate anomaly that causing prolonged dry season on the growth of PB 260 clone in Sembawa Research Centre Experimental Field. This research was conducted by comparing the growth of PB 260 clone during wet season and prolonged dry season. The result shows that under condition of 2015 El-Nino phenomenon, the growth rate of PB260 clone was decreased until 75%. The attemps to minimalize the effect of El-Nino on the growth of rubber clone was by selecting appropriate clone and location where the clone was planted, water conservation, and K fertilization with double dosage.